Expertise in action: The role and reception of advanced practice nurses in clinical settings - Aygul, Nagihan Sim; Senyuva, Emine (Nursing and Health Sciences Journal (NHSJ), 2025)
Advanced Practice Nurses (APNs) play a crucial and expanding role in modern healthcare by improving patient care quality and outcomes through their specialized knowledge and evidence-based practice. This study aims to explore the expectations and perceptions of both physicians and patients regarding APN services within clinical settings, based on their direct experiences. A phenomenological descriptive qualitative design was employed to capture the lived experiences of participants. Data was collected through semi-structured, face-to-face interviews and analyzed using thematic content analysis to identify key patterns and themes. The analysis revealed four primary themes: the utilization of specialized knowledge and skills, effective communication, problem-solving capabilities, and the importance of increasing the number of APNs working in clinical environments. Participants consistently reported that APN services contributed positively to care quality and patient satisfaction. Patients especially emphasized the need for APNs to apply their advanced expertise in practice and expressed a strong desire for greater APN availability in clinical settings. These findings highlight the essential role of APNs in enhancing healthcare delivery and suggest that healthcare institutions should actively support the growth and integration of APN roles to further improve patient outcomes and clinical effectiveness.